Implementation of gamification for international companies throughout rebranding: current and possible future approaches - Pazii, Dmytro (Національний технічний університет "Харківський політехнічний інститут", 2024)
In an ever-evolving and dynamic global business landscape, characterized by rapid technological advancements and shifting consumer prefe rences, international companies are continually seeking to enhance their branding strategies through the adop tion of innovative methodologies. One such approach that has garnered significant attention and adoption is the strategic integration of gamification throughout the rebranding process. Extensive market analysis indicates that gamification has emerged as a highly effective tool in not only capturing the attention of key stakeholders but also in fostering deeper engagement among employees, customers, and partners alike. This engagement, in turn, cultivates a pr ofound sense of involvement and loyalty towards the brand, thereby contributing to its long-term success and sustainability in the competitive marketplace. Furthermore, this article goes beyond mere theoretical discourse by presenting meticulously selected real-world examples that showcase the successful deployment of various gamification strategies within international companies undergoing rebranding initiatives. These strategies range from immersive interactive challenges to captivating social media contests, each tailored to suit the specific objectives and target audience of the rebranding campaign. By delving into both current industry practices and exploring potential future avenues, this comprehensive exploration sheds light on the transformative potential of gamification in rebranding efforts. It underscores the pivotal role played by gamification in driving organizational evolution and in fostering enduring brand resonance that transcends geographical boundaries and cultural barriers. As businesses continue to adapt to the ever-changing landscape, harnessing the power of gamification in rebranding endeavors emerges as a strategic imperative for maintaining relevance and achieving sustained growth in the global marketplace.

У постійно змінному та динамічному глобальному бізнес-ландшафті, що характеризується стрімкими технологічними досягненнями та змінними вподобаннями споживачів, міжнародні компанії постійно шукають способи поліпшення своїх стратегій брендування за допомогою інноваційних методик. Один із таких підходів, який здобув значну увагу та поширення, - стратегічне впровадження геймифікації в усіх етапах ребрендингу. Обширний аналіз ринку свідчить про те, що геймифікація виявилася дуже ефективним інструментом не лише для привертання уваги ключових зацікавлених сторін, але й для збудження глибшого зацікавлення серед співробітників, клієнтів та партнерів. Це зацікавлення, в свою чергу, сприяє глибшому включенню та лояльності до бренду, що в свою чергу сприяє його довгостроковому успіху та стійкості на конкурентному ринку. Більше того, ця стаття виходить за межі теоретичного дискурсу, презентуючи добірні реальні приклади, які демонструють успішне впровадження різних стратегій геймифікації в міжнародних компаніях, які здійснюють ініціативи з ребрендингу. Ці стратегії охоплюють інтенсивні інтерактивні виклики та захоплюючі конкурси у соціальних медіа, кожен з яких адаптований до конкретних цілей та цільової аудиторії кампанії з ребрендингу. Детальне дослідження як поточних практик галузі, так і потенційних майбутніх можливостей розкриває трансформаційний потенціал геймифікації в усіх зусиллях з ребрендингу. Це підкреслює ключову роль геймифікації у просуванні еволюції організації та в сприянні стійкому брендовому впливу, який перетинає географічні межі та культурні бар'єри. У міру того як бізнеси продовжують адаптуватися до постійно змінюючогося ландшафту, використання потенціалу геймифікації у зусиллях з ребрендингу визначається як стратегічна необхідність для збереження актуальності та досягнення стійкого зростання на глобальному ринку.
Впровадження гейміфікації для міжнародних компаній в процесі ребрендингу: поточні та майбутні можливі підходи
Keywords: international companies; rebranding; gamification; innovation; strategic changes; міжнародні компанії; ребрендинг; гейміфікація; інновації; стратегічні зміни